Tort liability arising from errors of medical analysis centers: A Comparative Analytical Study - Hadi Mohammed Abdullah; Ahmed Awrahman Ahmed (QALAAI ZANIST JOURNAL, 2020)
Medical analysis centers are part of the health care system of great importance in providing information about the health of a person, whether sick or healthy, in order to help reach a correct diagnosis and monitoring of his health condition, or accurate follow-up to assess the degree of change in the diseases and illnesses he suffers, and to detect Ailments and disorders in the vital and organic functions of the body, and the goal may be to prepare vaccines or vaccines that help prevent diseases, epidemics and infection, and since every person is exposed to disease, then he needs treatment, so the doctor is the first to think of him in order to resort to him to treat him, and the doctor In turn, and in order to reach a final diagnosis or to prepare an integrated plan for the treatment and care of the patient, medical analyzes are used in certain cases. As a first step in the list of diagnoses required to prove a clinical diagnosis, and then appropriate treatment is given to the patient, which contributes to his improvement, and may be reflected in the insufficiency and accuracy of the results of the tests and services provided by the analysis centers, or if there is an error in the result of these analyzes negatively on the process Diagnosis, treatment plan and patient health.